DESIGN OF AN INDUSTRIAL ELECTROCHEMICAL PLANT FOR WASTEWATER TREATMENT - SAILA, ABDELKADER (Journal of the Chilean Chemical Society, 2025)
Pollution load of water from urban networks is very notable, especially in large towns and industrial sites. In this context, the search for good solutions for this problem is highly important in current studies. Many chemical, physical and biological treatment methods have been developed. However, each of these methods has specific advantages. Therefore, the search for other solutions remains an exploited area. Among these new techniques to be developed are electrochemical methods. They present significant techniques in the elimination of organic and minerals pollutants; as well as, biological contaminants. In the present work, we have contributed to the design of an industrial electrochemical plant for the treatment of different pollutants based in previous studies. Firstly: we carried out an exhaustive study on the electrochemical processes used in the elimination of different pollutants. We approved a simulation to design a simple form of an electrochemical reactor. Furthermore, we regrouped the necessary information on electrode materials and experimentally confirmed the use of a general economic electrode. This investigation allowed constructing an efficient database to design an industrial scale electrochemical processing reactor, from which we used economic and efficient materials.